VD_FINDINFO HC / 2014 / 894 vom 26. September 2014 - VD Tribunal cantonal (2014)
PREUVE À FUTUR, RECOURSCPC, APPELCPC, DÉCISION D'IRRECEVABILITÉ | 158 al. 2 CPC (CH), 308 CPC (CH), 319 let. b ch. 2 CPC (CH)